2007
DOI: 10.1002/adem.200700004
|View full text |Cite
|
Sign up to set email alerts
|

Equal Channel Angular Pressing Die Outer Corner Angle Influence on Flow and Strain Homogeneity

Abstract: Equal channel angular pressing (ECAP) is the most promising severe plastic deformation (SPD) technique for fabrication of bulk ultrafine grain materials, [1] compaction of powders, [1,2] and property enhancement of tubular materials. [3] The strain induced during the ECAP is mainly influenced by tool angles: channel angle 'j' and outer corner angle 'w' according to the equations developed from slip line theory [4] and geometrical approach. [5] In addition to that the friction between the die and sample, work/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The shear strain in the bottom region is increased due to the friction effect and is reduced due to strain hardening effect. Strain hardening also generates a corner gap between the workpiece and die, which has been widely discussed in earlier studies [3,9,13,14]. This uniform deformation along the width direction is the main reason for the lack of bending.…”
Section: Finite Element Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The shear strain in the bottom region is increased due to the friction effect and is reduced due to strain hardening effect. Strain hardening also generates a corner gap between the workpiece and die, which has been widely discussed in earlier studies [3,9,13,14]. This uniform deformation along the width direction is the main reason for the lack of bending.…”
Section: Finite Element Analysismentioning
confidence: 92%
“…To fabricate the bulk ultrafine grain materials, variety of die designs with different tool angles, and different processing routes have been used [1]. The strain distribution and deformation behavior during the ECAP, which was influenced by tool angles, friction, and material behavior, was studied through finite element analysis (FEA) [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…corner. And because of the force condition of the material inside and outside the corner is inconsistent [11], the flow rate at inner corner is lower than that at outer corner. So the square gird turns into sector gird.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The research was supported by Key Fund Project of Sichuan Provincial Department of Education (NO.11ZA001), Key Laboratory of fluid and power machinery, ministry of education (SBZDPY- [11][12][13][14][15][16]) and open research fund of key laboratory of Sichuan, Xihua University (NO.SZJJ2009-018 and SZJJ2012-001).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recently, it was found that the strain homogeneity of the ECAP process dictates the mechanical properties of the deformed materials. 26,27) Hence, it is also necessary to understand the strain homogeneity of ECAP-FE combined processes. Thus, in the current study, the deformation flow, strain homogeneity, and load requirements of FE and ECAP combined processes of FE+ECAP and ECAP+FE are numerically investigated and compared with those values in individual FE and ECAP processes.…”
Section: Introductionmentioning
confidence: 99%